Postactivation potentiation improves performance in a resistance training session in trained men - Alves, R. R.; Viana, R. B.; Silva, M. H.; Guimarães, T. C.; Vieira, C. A.; de AT Santos, D.; Gentil, P. R. (The Journal of Strength and Conditioning Research, 2021)
This study aims to analyze the influence of postactivation potentiation (PAP) on performance during a resistance training (RT) session in trained individuals. Fourteen trained men (25.0 ± 3.5 years; 89.9 ± 16.3 kg; 1.77 ± 0:08 m; 28.0 ± 4.0 kg·m-2; and 5 ± 4 years of RT experience) were tested in 2 situations: with PAP and without PAP (CON). Both situations involved 3 sets of the bench press exercise performed to muscle failure at 75% of the 1 repetition maximum load and with 1.5-minute interval between sets. Total work was greater (p < 0.001) for PAP (1,601 ± 504 kg) than for CON (1,379 ± 364 kg). The number of repetitions performed in the first and second sets of PAP (11.5 ± 3.1 and 6.5 ± 1.9, respectively) were greater (p < 0.05) than those performed in CON (10.4 ± 2.7, 5.5 ± 1.8, respectively). No significant difference was found in the number of repetitions in the last set between the situations. The present study suggests that PAP might be beneficial to improve total work and performance during multiple sets of RT in trained men. Therefore, PAP might be used during RT to promote higher total work and potentially increase results over long term. Thus, the protocol can use in sports centers, fitness centers, and gyms per coaches and athletes to increase performance and total work in trained individuals.